Implementation DeLone & McLean IS Success Model for Research and Community Service Management Information System Evaluation - Awang Hendrianto Pratomo; Riza Prapascatama Agusdin; Sylvert Prian Tahalea; Nur Heri Cahyana (Techno LPPM, 2021)
SRIKANDI is an information system managed by LPPM that manages research and lecturer service within the UPN "Veteran" Yogyakarta. SRKANDI in its implementation has never been evaluated, therefore in this reserach SRIKANDI was evaluated. The evaluation was carried out using the DeLone & McLean IS Success Model with 150 data obtained from distributing questionnaires to lecturers who had used SRIKANDI. The approach used in this research is quantitative by using regression analysis to test the twelve hypotheses that exist with the successful implementation of SRIKANDI as an information system.